Analýza vztahu volných lehkých řetězců κ/λ a páru těžkých/lehkých řetězců imunoglobulinu ke stratifikaci mnohočetného myelomu podle Mayo Stratification of Myeloma and Revised International Staging System - Ščudla, Vlastimil; Balcárková, Jana; Lochman, Pavel; Vincová, Miroslava; Pika, Tomáš; Minařík, Jiří; Zapletalová, Jana; Jarošová, Marie (Vnitrni lekarstvi, 2016)
INTRODUCTION: Assessment of serum levels of free light chains (FLC-κ and FLC-λ) and recently heavy/light chain pairs of immunoglobulin (HLC-κ and HLC-λ) and their ratio (FLC-r and HLC-r) has significantly enriched traditional algorithm of multiple myeloma (MM) evaluation. The aim of the presented study was to assess the relationship of classical prognostic parameters of MM, standard FLC-κ/λ and HLC-κ/λ ratio ((s)FLC-r and (s)HLC-r), modified ratio of "involved/uninvolved" FLC and HLC ((m)FLC-r and (m)HLC-r ), the difference between "involved - uninvolved" FLC and HLC (FLC-dif. and HLC-dif.) to current stratification models of MM based on the result of cytogenetic analysis. PATIENTS AND METHODS: In a group of 97 patients with MM we assessed serum levels of FLC by FreeliteTM method, and we calculated (s)FLC-r, (m)FLC-r and FLC-dif. indices by HevyliteTM method. For cytogenetic analysis we used FICTION (fluorescence immunophenotyping and interphase cytogenetics as a tool for the investigation of neoplasms). For MM stratification we used standard staging systems according to Durie-Salmon (D-S) and International Staging System (ISS) as well as novel stratification systems based on the results of cytogenetic analysis, ie. "Mayo Stratification of Myeloma and Risk-Adapted Therapy" (mSMART) and "Revised International Staging System" (R-ISS). RESULTS: Stratification mSMART and R-ISS has significantly different representation of "standard" or "low-risk" (71, 15.5, 11.3 a 29.9 %), "intermediate risk" (15.5, 53.6, 34 a 33 %) and "high risk" patients (13.4, 30.9, 54.7 a 37.1 %) compared to standard staging systems. mSMART stratification was compared to prognostic factors of MM (Hb, albumin, β(2)-M, creatinine and LDH), and the only significant relationship was found in the case of β(2)-M, R-ISS had relationship only to Hb and creatinine. In the case of D-S staging we found significant relationship of stages 1-3 and substages A and B to the levels of (m)FLC-r, FLC-dif. and (m)HLC-r, ISS had moreover relationship to k HLC-dif. and MIg concentration. Analysis of mSMART stratification showed primarily significant relationship of risk categories 1-3 to (m)FLC-r and (s)HLC-r indices, and R-ISS to (m)HLC-r index and MIg concentration. In both cytogenetics-based stratifications there was a lack of relationship to (s)FLC-r, FLC-dif. and HLC-dif. indices. CONCLUSION: Comparison of the results of standard staging systems according to D-S and ISS with cytogenetics based models mSMART and R-ISS showed different representation of risk groups, and significantly different relationship to classical prognostic factors together with original relationship of sMART stratification to (m)FLC-r and (s)HLC-r, and R-ISS to (m)HLC-r and MIg concentration.
Keywords: Immunoglobulin Light Chains; dospělí; Immunoglobulin lambda-Chains; Female; Adult; ženské pohlaví; lehké řetězce imunoglobulinů; lidé; mnohočetný myelom; Aged, 80 and over; imunoglobuliny - lambda-řetězce; prognóza; Male; Aged; Prognosis; lidé středního věku; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Middle Aged; Humans